2002
DOI: 10.1007/bf03402077
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Natural Product Compound Enhances cAMP-Regulated Chloride Conductance of Cells Expressing CFTRΔF508

Abstract: Background: Cystic fibrosis (CF) results from mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, which encodes a chloride channel localized at the plasma membrane of diverse epithelia. The most common mutation leading to CF, ⌬F508, occurs in the first nucleotide-binding domain (NBD1) of CFTR. The ⌬F508 mutation disrupts protein processing, leading to a decreased level of mutant channels at the plasma membrane and reduced transepithelial chloride permeability. Partial correction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…Thus, much effort has been expended in attempting to find a clinically viable pharmacological means of achieving trafficking of the mutant protein to the plasma membrane as a potential cure for a large percentage of cystic fibrosis cases (53,54). In a similar manner, a pharmacological chaperone that can rescue a3 R444L , especially if usable during early infancy, or in utero, might be of benefit to patients afflicted with a3 R444L -mediated ARO.…”
Section: R444lmentioning
confidence: 99%
“…Thus, much effort has been expended in attempting to find a clinically viable pharmacological means of achieving trafficking of the mutant protein to the plasma membrane as a potential cure for a large percentage of cystic fibrosis cases (53,54). In a similar manner, a pharmacological chaperone that can rescue a3 R444L , especially if usable during early infancy, or in utero, might be of benefit to patients afflicted with a3 R444L -mediated ARO.…”
Section: R444lmentioning
confidence: 99%
“…Filtration and vacuum concentration of the resulting solution led to a dark greenish extract (yield: 15.5%). A bioassay-guided chromatographic fractionation over silica gel of the above extract, followed by purification using silica gel column chromatography resulted in the isolation of three new limonoids, rubescins A-C (1-3) and known compounds including, havanensin type limonoid TS3 (4), 7) β-sitosterol and stigmasterol as described in Experimental. The known compounds were identified by comparison of their spectroscopic data ( 1 H-, 13 C-NMR and mass spectra) with those reported in literature.…”
Section: Resultsmentioning
confidence: 99%
“…The known compounds were identified by comparison of their spectroscopic data ( 1 H-, 13 C-NMR and mass spectra) with those reported in literature. 7) Rubescin A 1, mp 234-236°C, [ quaternary carbons. These data suggested that 1 was a tetranorterpenoid similar to havanensin type limonoid TS3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological interventions attempt to correct defective ion transport among other pulmonary phenotypes. Recent strategies make use of natural food components because of their ready accessibility and low toxicity (deCarvalho et al, 2002;Bjarnsholt et al, 2005;Egan et al, 2004). These compounds act in different ways, such as correcting the trafficking defect of mutant CFTR or potentiating residual CFTR activity (Kunzelmann and Mall, 2003;Moran and Zegarra-Moran, 2005;Van Goor et al, 2006).…”
mentioning
confidence: 99%